P25 Erdheim-Chester disease: a rare histocytosis masked as IgG4 disease. (20th April 2020) - Das, Dhivya; Jones, Sharon
Abstract: Background: Erdheim-Chester disease (ECD) is a rare non-inherited, non-Langerhans form histiocytosis reclassified as a histiocytic neoplasm was first described in 1930 by Jakob Erdheim and William Chester. Only 500 cases were reported. Onset is usually between 50 to 70 years old. Male to female ratio is 3:1. Symptoms include long bone pain, fever, weight loss, exophthalmos, papilledema, headaches, cranial nerve palsies and sensory disturbances. Skeletal Abnormalities includes bilateral and symmetric cortical osteosclerosis of long bones. Cardiovascular involvement includes a 'coated aorta' which can involve renal arteries leading to reno-vascular hypertension. Pulmonary and retroperitoneal fibrosis has been reported. Methods: We present a 90 year old gentleman with a complicated history of diplopia, proptosis with large retrobulbar orbital masses (confirmed on CT orbits) increasing in size over 2 years. He was symptomatic with bone pain, recurrent falls, dizziness and shortness of breath. He had a background history of pulmonary embolism, atrial fibrillation, hypertension and osteoporosis. On examination, no joint synovitis or lymphadenopathy noted. Chest examination revealed mild inspiratory crackles. Results: CRP was recorded at 150mg/L. ANA, ENA, ANCA, anti-DsDNA, RF, anti-MCV antibodies were negative. IgG4 levels were normal. Pulmonary Function tests showed a restrictive Pattern - FEV1/FVC - 64%, FVC - 68%, TLC - 75%, TLCO - 68% predicted. CT Chest reported aortitis and mild undifferentiated pulmonary fibrosis. CT aorta done subsequently reported extensive soft tissue changes of the abdominal and thoracic Aorta which extended to the renal hila causing bilateral hydronephrosis. There was confirmed retroperitoneal Fibrosis and widespread para-aortic lymphadenopathy. He was stented by the urologists for hydronephrosis. Orbital biopsy of his left eye revealed xanthogranulomatous inflammation with widespread foamy histiocytes (CD68 positive). S100 and CD1a were negative. This confirms a clinical correlation of ECD. Further multidisciplinary discussions suggested that he stays on high dose prednisolone of 30mg daily. Localised radiotherapy was successful in debulking his orbital lesions. Chemotherapy was discussed but he does not wish for this. Conclusion: Differential diagnoses for ECD include IgG4 disease, Granulomatosis with polyangiitis, Takayasu's arteritis, Langherhan Cell histiocytosis, or malignancies. Tissue diagnosis describes infiltration of foamy histiocytes, lymphocytes and lipid laden macrophages. It is distinguished by immunohistological characteristics (ECD positive for CD68, negative for CD1a and S-100 protein) in 80 percent of cases. Serum Assay Samples can show high IFN-alpha, IL1, IL-6 and IL-12 titres. First line treatment is pegylated IFN-alpha. Bisphosphonates can alleviate bone pain. Cladribine has helped those with orbital involvement. Anakinra or Inflixamab improves symptoms of mild forms of ECD. Vemurafenib is used for patients with the BRAFV600 proto-oncogene mutation. PET scans are recommended for disease activity assessment. ECD has a variable prognosis but poorer in those with CNS involvement. With treatment, the mortality rate is 26% and 5-year survival is 68%. Disclosures: D. Das None. S. Jones None.